2010
DOI: 10.1128/aem.03105-09
|View full text |Cite
|
Sign up to set email alerts
|

CandidatusAnadelfobacter veles” and “CandidatusCyrtobacter comes,” Two NewRickettsialesSpecies Hosted by the Protist CiliateEuplotes harpa(Ciliophora, Spirotrichea)

Abstract: The order Rickettsiales (Alphaproteobacteria) is a well-known group containing obligate endocellular prokaryotes. The order encompasses three families (Rickettsiaceae, Anaplasmataceae, and Holosporaceae) and a fourth, family-level cluster, which includes only one candidate species, "Candidatus Midichloria mitochondrii," as well as several unnamed bacterial symbionts. The broad host range exhibited by the members of the "Candidatus Midichloria" clade suggests their eventual relevance for a better understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 48 publications
2
50
0
2
Order By: Relevance
“…However, the bacterial symbiont's lack of an equivalent of the perialgal vacuole membrane suggests that it is digestion-resistant, much like some other bacteria in free-living amoebae [29] and ciliates [e.g. 10,18,19,64,67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the bacterial symbiont's lack of an equivalent of the perialgal vacuole membrane suggests that it is digestion-resistant, much like some other bacteria in free-living amoebae [29] and ciliates [e.g. 10,18,19,64,67].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, our knowledge of the diversity of bacteria associated with ciliates has increased significantly, primarily as a result of extensive molecular investigations of some commonly occurring species of the genera Paramecium and Euplotes. These studies have demonstrated that most bacterial symbionts belong to one of four classes of the phylum Proteobacteria, namely Alphaproteobacteria (including pathogenic Rickettsia) [2,8,9,18,19,21,22,51,59,60,62,64,67,69], Betaproteobacteria [58,63,66,68], Gammaproteobacteria [4,10,48,53] and Deltaproteobacteria [15]. Associations between ciliates and bacteria of other phyla seem to be infrequent, for example, Verrucomicrobia [42] and Firmicutes [54].…”
Section: Introductionmentioning
confidence: 99%
“…Recent nucleotide sequence additions from this order of bacteria to public databases refines the placement of the 16S rRNA sequence in the genera classified as "incertae sedis," with low support branching probability (64.76%) in the family Holosporaceae (Fig. 1A) (15)(16)(17)(18)(19). Both Holospora spp.…”
mentioning
confidence: 99%
“…Бактерии группы MALOs (midichloria and like organisms), филогенетически близкие с «Candidatus M. mitochondrii», продемонстриро-вали связь с широким кругом хозяев: от члени-стоногих (клещи, блохи, клопы и жуки) до ин-фузорий, амеб, губок, рыб и различных живот-ных, включая человека [1,6,10,17,19,21,23,44]. При изучении последовательностей гена 16S рРНК группа MALOs образовала монофилети-ческую группу, структурированную на отдель-ные подгруппы (клады), которые могут пред-ставлять новые рода, и заняла позицию на уров-не описанных семейств из порядка Rickettsiales, что привело к предложению выделить новое семейство -«Candidatus Midichloriaceae» [23].…”
Section: классификация и номенклатураunclassified
“…Применение молекулярно-биологических методов в последние десятилетия привело к описанию новых видов риккетсий, включая патогенные для человека виды [27], а также некультивируемых в лабораторных условиях микроорганизмов из порядка Rickettsiales [6,14,15,22,39,44], которые в соответствии с ре-комендациями ICSB (International Committee of Systematic Bacteriology) были классифици-рованы как «Candidatus sp.» [24]. Эндосимби-онт иксодовых клещей Ixodes ricinus «Candidatus Midichloria mitochondrii» требует особого вни-мания со стороны исследователей, так как яв-ляется единственной из известных в настоя-щее время бактерий, которая была обнаружена внутри митохондрий животных [4,34,36].…”
Section: Introductionunclassified